Insects in Scientific Research: A Philosophical Examination through the Lens of the 3Rs - Tsikas, Angelos (Bioethica, 2025)
This essay examines the ethical implications of using insects in scientific research through the framework of the 3Rs—Replacement, Reduction, and Refinement. Historically, ethical considerations in research have focused on vertebrates, but increasing evidence suggests that insects may possess more complex cognitive and sensory capacities than previously thought, raising moral questions about their treatment. The principle of Replacement is discussed in relation to alternative methods such as in silico models, in vitro systems, and biomimetics, which offer promising ways to reduce the reliance on live insects. However, these alternatives are not yet advanced enough to fully replicate the complexity of biological processes in insects. Reduction, which aims to minimize the number of animals used in research, requires more precise statistical techniques and better experimental design to balance ethical concerns with scientific rigor. Finally, Refinement emphasizes minimizing suffering and improving welfare, including the use of anesthesia and appropriate euthanasia techniques, although research into insect welfare and euthanasia methods remains limited. Through an analysis of utilitarianism, deontological ethics, and virtue ethics, this essay argues that ethical considerations must extend to insects. Despite their differences from vertebrates, the 3Rs should guide insect research to reduce harm and promote responsible scientific inquiry.